Predictors for e-government adoption: integrating TAM, TPB, trust and perceived risk. Issue 1 (6th February 2017) - Xie, Qijun; Song, Wei; Peng, Xiaobao; Shabbir, Muhammad
Abstract : Purpose: The present research aims to identify determinants for citizen' behavioural adoption of e-government, explore relationships among these variables and investigate whether the proposed model can provide a more comprehensive manner to understand the adoption of e-government. Design/methodology/approach: First, a survey is administered to collect data, then the Cronbach's alpha is assessed for internal consistency of measurement scales; second, confirmatory factor analysis is conducted to evaluate the measurement model; finally, a structural equation model is used to test the proposed hypotheses and explore the determinants of e-government adoption. Findings: Results indicate that the proposed model is a stable model with powerful explanatory of variation. In addition, some new relationships in the e-government context are found, whose disposition to trust has positive effect on social norms, whereas perceived risk negatively influences perceived behaviour control. Moreover, other key dominants have been investigated. Originality/value: The findings have enabled us to better understand factors affecting intention and also provided a solid theoretical research model for future study.